Resistant stomach ulcer at Cushing disease: clinical case - N. V. Novozhilov; Yu. O. Shulpekoa; S. V. Mironov; Ye. K. Baranskaya; A. A. Sheptulin; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of the publication. To present clinical case of Cushing disease, with resistant large stomach ulcer.Original positions. Hypercorticoidism is one of the causes of treatment-resistant stomach ulcers that is due to increase in gastric secretion and depression of collagen formation under the effect of hydrocortisone. Since 2009 we follow up the patient (female, 47 years old) who for the first time addressed to the doctor with complaints of pain and muscle weakness, mainly — of lower extremities, and also hip, ankle joints pain, which essentially complicated locomotion capacity. Initially these symptoms were inaccurately attributed to osteoarthrosis, thus patient received nonsteroid anti-inflammatory drugs (NSAID) and high doses of Kenalog. Later classical symptoms of hypercorticoidism - characteristic changes of the face, visceral obesity, striae, systemic hypertension and diabetes mellitus became obvious. Within over half a year patient had large antral ulcer of the stomach (periodically turning to giant) with signs of occult bleeding. Chronic ulcer was characterized by complete absence of granulations and striae-shaped changes of surrounding mucosa. During the further investigation: low-dose dexamethasone suppression test, magnetic-resonance tomography (MRI) and computer tomography (CT) of the brain and abdominal cavity data, favoring the Cushing disease (ACTH-producing pituitary adenoma), was obtained. Pathogenesis of chronic stomach ulcer is complex: effect of H.pylori infection, drugs (NSAID, steroids) and hypercorticoidism. Antihelicobacter eradication treatment, complete cancellation of NSAID and steroids, treatment by high doses of proton pump inhibitors, Н2-blockers, bismuth subcitrate did not result in ulcer healing. In January, 2010 the ulcer bleeding developed (Forrest stage IIс), that was stopped by conservative treatment. Intravenous injection of esomeprazole allowed to decrease the size of ulcer and promoted its further healing. After transsphenoidal adenomectomy improvement of general well-being, weight loss, decrease of muscle weakness, improvement of parameters of glucose metabolism and blood pressure were marked; the stomach ulcer did not recur.